Promotion of Copper Corrosion Inhibition by Application of a Square Wave Potential Regime to Copper Specimens in Polyvinylpyrrolidone Solutions - Hourania,Mohammed K. (2016)
Enhancement of corrosion inhibition of copper by polyvinylpyrrolidone (PVP) upon application of a square wave potential regime to copper specimens was investigated. The results indicated a marked decrease of copper corrosion rate upon application of a square wave to copper specimens in PVP - containing solutions. The inhibition enhancement was found to increase when increasing PVP concentration, and with a larger time of exposure with application of the square wave potential regime. A 500 Hz frequency was the optimal frequency for promotion of inhibition by PVP. SEM micrographs revealed that application of the square wave converted the dendritic coverage of PVP to a more uniform layer of PVP at copper surface. The enhancement of corrosion inhibition by application of the square wave might be explained on basis of the enhanced adsorption of PVP onto copper surface by application of the square wave potential regime. Application of square wave potential regime apparently influences the PVP adsorption coverage at the copper surface.